Identifikasi dan Analisis Filogenetik Portunus trituberculatus Dari Perairan Cirebon Menggunakan Barkode Gen COI Mitokondrial - Subagiyo Subagiyo; Retna Handayani; Rahayu Rahayu; Triandala Mada Sibero (Jurnal Kelautan Tropis, 2018)
Phylogenetic Identification and Analysis Portunus trituberculatus from Cirebon Coast Using the COI Barcode  Mitochondrial Portunus trituberculatus spesimen from Cirebon coast were successfully identified using mitochondrial DNA cytochrome c oxydase subunit I (COI) genes. Analysis of haplotype distribution of P. trituberculatus along with the same species from China, Korea, India and the Philippines obtained from NCBI gene banks resulted 17 haplotypes from 25 specimens. Haploid diversity was 0.943 + 0.031 and nucleotide diversity was 0.04821 + 0.0139. The Cirebon specimen is in separated haplotipe from the others. The results of phylogenetic analysis showed that the 25 specimens were clustered into 3 clusters in 2 different lineages with percentages genetic distance were 12.76%, 14.24% and 14.33% respectively. The genetic distance within each cluster ranges from 0 - 2.92%. The Cirebon crab specimen is in the same cluster as the Philippine specimen with 1% genetic distance.  Spesimen rajungan Portunus trituberculatus dari perairan Cirebon berhasil diidentifikasi menggunakan gen  mitochondrial DNA cytochrome c oxidase subunit I (COI). Analisis distribusi haplotipe dengan data P trituberculatus yang berasal dari China, Korea, India dan Filipina yang diperoleh dari data genebank NCBI didapatkan 17 haplotipe dari 25 spesimen, dengan keragaman haploid 0,943 +0.031 dan keragaman nukleotida 0,04821+0.0139. Spesimen Cirebon merupakan haplotipe yang terpisah dari yang lainnya. Hasil kajian filogenetik menunjukkan 25 spesimen mengelompok ke dalam 3 kluster dari 2 garis keturunan yang berbeda dengan jarak genetik berturut turut  12,76 %, 14,24 % dan 14,33 %. Jarak genetik di dalam masing-masing kluster berkisar antara 0 – 2,92 %.  Spesimen rajungan Cirebon berada pada garis keturunan dan kluster yang sama dengan spesimen Filipina dengan jarak genetik 1%.